Eficácia do wii-fit no equilíbrio de crianças com paralisia cerebral: série de casos - Mendonça, Jislandia Menezes (2022)
Children with cerebral palsy (CP) have several functional deficits, including limited balance. Virtual reality through the use of video games can be an innovative therapeutic tool to improve the balance of these children in a playful, varied and safe way. The Wii Fit Plus ® is a package for the Nintendo console that comes with a strength platform and offers games that encourage aerobic, muscle conditioning, balance and strength exercises. In public pediatric physical therapy care in the SUS, there is a waiting list, where most of this list is composed of children with CP, the use of an efficient and low-cost therapeutic tool would help to speed up the care of these children in the SUS. The objective of this study is to determine the effect of Wii Fit Plus ® on the balance of children with CP who are on the waiting list for physiotherapeutic care at SUS. Children with CP recruited from the waiting list of the medical specialty center in Lagarto, aged between 5 and 18 years, classified in GMFCS 1 to 3 and able to understand simple commands, were selected to participate in the research. The instruments used to assess balance were Time Up and Go (TUG), functional range and Pediatric Berg Balance Scale. This study follows the single-subject analysis model with repeated measures in three ABA phases, where A1 is the pre-treatment phase, B is the during-treatment phase, and A2 is the post-treatment phase. Each child was evaluated nine times, three times for each outcome and in each phase. The analysis of the results was performed using the band method with 2 standard deviations, if a point falls outside the band it has a significance of p<0.05. The results observed in the Berg scale were positive for all six volunteer children, but one of them already had a very high score and because of the measurement ceiling, it was not possible to verify changes. The Functional Reach and TUG, despite not having significant results for all six children, showed satisfactory results for most of them. Through the results of this study, we concluded that the Wii Fit Plus ® is an effective physical therapy tool to improve the balance of children with CP and should be used in public care in the SUS.